UTILIZATION OF PRE-PREPARED SAMPLES OF TEXTILE COMPOSITIONS TO DESIGN AND PRODUCE HOME SUPPLEMENTS (Journal of Pharmaceutical Negative Results, 2023)
The study aims to test the creative ability to reuse prefabricated textile parts in the production of home supplements that bear both functional and aesthetic meanings. The study used the analytical descriptive curriculum. The sample of the study consisted of 110 residents of the governorate of El Jarshi, Saudi Arabia. The questionnaire was used as a tool for study, and after data collection, it was analyzed by appropriate statistical analysis methods using SPSS. The results indicated that about 86% of the target groups use leisure time for manual work, and that about two-thirds of the sample, uses fabric pieces for decoration. This result is important and demonstrates an awareness among the target groups of the importance of reusing prefabricated fabric parts, and that the reuse of prefabricated fabric parts is of high importance (79.1%).